Teachers and Technology: The Evolving Role of Educators in AI-Enhanced Learning Environments - Muhammad Umar; Dr. Saima Shaheen; Tabassum Shehzad; Sahibzadi Sidrat ul Muntaha; Sajid Khan (Indus Journal of Social Sciences, 2025)
With the advancement of artificial intelligence (AI) in the delivery of education, the position of the teacher is also changing. This research explores the adoption of AI-based learning in secondary schools and specifically looks at the awareness of educators with AI tools, the level of integration, perceived advantages and disadvantages, and support structures. The quantitative design of the study involved administering questionnaires to 150 teachers in different regions, whereby descriptive and inferential statistics were employed to analyse the information received. It reveals that, even if technologies like, auto-grading, learning management systems are popular and receive positive student perceptions, more advanced uses of the technologies like predictive analytics are not incorporated fully because of lack of confidence and little training. This study also shows that schools require institutional resources such as workshops, technical support and policies to effectively initiate AI. Teachers’ preferences include practical, interactive training and reveal their emergent professional role in using AI for interpreting results, regulating ethical issues, and co-designing the AI-enhanced instruction. The study underscores the necessity of emergent systemic solutions, ethical competencies and policy measures to transform AI into a tool that empowers education instead of decreasing their authority in the process of teaching. This paper thus adds to the developing literature on human-AI interaction in learning, with a plea for moderation, or a balanced approach where the teacher remains central.